Inducible T-Cell Co-Stimulator Impacts Chronic Graft-Versus-Host Disease by Regulating Both Pathogenic and Regulatory T Cells - Zhang, Mengmeng; Wu, Yongxia; Bastian, David; Iamsawat, Supinya; Chang, Jinsam; Daenthanasanmak, Anusara; Nguyen, Hung D.; Schutt, Steven; Dai, Min; Chen, Fangping; Suh, Woong-Kyung; Yu, Xue-Zhong (Frontiers in Immunology, 2018)
The incidence of chronic Graft-versus-Host disease (cGVHD) is on the rise and still the major cause of morbidity and mortality among patients after allogeneic hematopoietic stem cell transplantation (HCT). Both donor T and B cells contribute to the pathogenesis of cGVHD. Inducible T-cell co-stimulator (ICOS), a potent co-stimulatory receptor, plays a key role in T-cell activation and differentiation. Yet, how ICOS regulates the development of cGVHD is not well understood. Here, we investigated the role of ICOS in cGVHD pathogenesis using mice with germline or Treg-specific ICOS deficiency. The recipients of ICOS-/- donor grafts had reduced cGVHD compared to wild type controls. In recipients of ICOS-/- donor grafts, we observed significant reductions in donor T follicular helper (Tfh), Th17, germinal center B-cell, and plasma cell differentiation, coupled with lower antibody production. Interestingly, regulatory T cells (Tregs), including follicular regulatory T (Tfr) cells, were also impaired in the absence of ICOS. Using ICOS conditional knock-out specific for Foxp3+ cells, we found that ICOS was indispensable for optimal survival and homeostasis of induced Tregs during cGVHD. Furthermore, administration of anti-ICOS alleviated cGVHD severity via suppressing T effector cells without affecting Treg generation. Taken together, ICOS promotes T- and B-cell activation and differentiation, which can promote cGVHD development; however, ICOS is critical for the survival and homeostasis of iTregs, which can suppress cGVHD. Hence, ICOS balances the development of cGVHD, and could offer a potential target after allo-HCT in the clinic.